2020
DOI: 10.1111/fog.12475
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of fish eggs collected off northwestern Cuba and across the Florida Straits demonstrates egg transport by mesoscale eddies

Abstract: Identifying spawning sites for broadcast spawning fish species is a key element of delineating critical habitat for managing and regulating marine fisheries. Genetic barcoding has enabled accurate taxonomic identification of individual fish eggs, overcoming limitations of morphological classification techniques. In this study, planktonic fish eggs were collected at 23 stations along the northwestern coast of Cuba and across the Florida Straits to United States waters. A total of 564 fish eggs were successfully… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…DNA barcoding, which delimits species based on a segment of the mitochondrial cytochrome c oxidase subunit I (COI), has been widely used to identify fish eggs (Chen et al., 2021 ; Hofmann et al., 2017 ; Hou et al., 2020 ; Kerr & Breitbart, 2021 ; Kerr et al., 2020 ; Leyva‐Cruz et al., 2016 ). For example, Leyva‐Cruz et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…DNA barcoding, which delimits species based on a segment of the mitochondrial cytochrome c oxidase subunit I (COI), has been widely used to identify fish eggs (Chen et al., 2021 ; Hofmann et al., 2017 ; Hou et al., 2020 ; Kerr & Breitbart, 2021 ; Kerr et al., 2020 ; Leyva‐Cruz et al., 2016 ). For example, Leyva‐Cruz et al.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kerr et al. ( 2020 ) used DNA barcoding to identify fish eggs collected from northwestern Cuba and across the Florida Straits, assigning 564 fish eggs to 89 species. Therefore, it has been demonstrated that DNA barcoding can effectively identity fish eggs to species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Once the plankton sample is taken back to the lab, fish eggs are picked out from the wide variety of planktonic organisms using microscopes and forceps ( 5 ). Since fish eggs are usually clear spheres with few distinguishable characteristics, accurate visual identification of the species is difficult and often unreliable ( 6 ), leading scientists to use DNA barcoding to identify the eggs down to species level.…”
Section: Introductionmentioning
confidence: 99%